A Key Exchange Approach for Proficient and Secure Routing in Mobile Adhoc Networks - Raghavendar Raju, L; Reddy, C R K Reddy (International Journal of Interactive Mobile Technologies (iJIM), 2017)
Mobile ad hoc networks (MANETs) are collection of wireless mobile devices with restricted broadcast range and resources. Communication is achieved by relaying data along appropriate routes that are dynamically discovered and maintained through collaboration between the nodes. Discovery of such routes is a major task, both from efficiency and security point of view. This paper presents a proficient and secure routing, based on asymmetric authentication using key exchange approach (KEA). The proposed mechanism ensures secure routing and quality of service in MANETs and minimizes the network overhead. The KEA mechanism can be effectively used to develop a new routing protocol for Mobile Adhoc Networks which will provide maximum security against all kinds of attacks. In this paper, KEA is compared with other secure routing protocols like EEACK, AODV, and ARIADANE, to evaluate the efficiency of KEA in Ad Hoc Networks. The empirical results shows that there is an increase of 20% packet delivery ratio and a reduction of 10% routing overhead.